Role of Inflammatory Risk Factors in the Pathogenesis of Streptococcus pneumoniae - Sohail, Ifrah; Ghosh, Sumit; Mukundan, Santhosh; Zelewski, Susan; Khan, M. Nadeem (Frontiers in Immunology, 2018)
Streptococcus pneumoniae (Spn) is a colonizer of the human nasopharynx (NP), causing a variety of infections in humans including otitis media, pneumonia, sepsis, and meningitis. The NP is an immune permissive site which allows for the persistence of commensal bacteria. Acute or chronic respiratory airway inflammation constitutes a significant risk factor for the manifestation of Spn infections. The inflammatory conditions caused by an upper respiratory viral infection or respiratory conditions such as allergic asthma and chronic obstructive pulmonary disorders (COPDs) are implicated in the dysregulation of airway inflammation and tissue damage, which comprise the respiratory barrier integrity. These immune events promote bacterial outgrowth leading to Spn dissemination and invasion into the bloodstream. Therefore, suppression of inflammation and restoration of respiratory barrier integrity could contain Spn infections manifesting in the backdrop of an inflammatory disease condition. The gained knowledge could be harnessed in the design of novel therapeutic interventions to circumvent Spn bacterial infections.